Contemporary Approaches to Research in TESOL - Sardar M Anwaruddin (Journal of Education and Learning (EduLearn), 2013)
Teaching English to Speakers of Other Languages (TESOL) is one of the largest educational enterprises in the world. Tens of thousands of teachers—both native and non-native speakers of English—are engaged in TESOL across the world. This large population of teachers depends heavily on academic researchers for developing their knowledge base. Although it is evident that teachers who engage in classroom research are more aware of their practices and better able to facilitate student learning, teacher-research is a minority activity in the field of TESOL. In this article, I briefly discuss TESOL practitioners’ conceptions of research. Then, I focus on a dichotomous relationship between qualitative and quantitative approaches to research, and review some contemporary orientations to TESOL research. I conclude the article with a recommendation that TESOL practitioners engage in action research for their professional development as well as their students’ increased learning of the target language.